Analysis of Financial Planning and Control at the Gowa Regency Trade and Industry Service - Mutiara, Mutiara; Ismail Badollahi; Amelia Rezki Septiani Amin (International Journal of Economic Research and Financial Accounting, 2024)
This research aims to determine Financial Planning and Control at the Gowa Regency Trade and Industry Service. This research using this type of research qualitative descriptive Which dimana inform pada this research adthe officer District Trade and Industry Office Gowa as many as 3 informants. The results of this research show that the Gowa Regency trade and industry office has good financial planning because it has been carried out routinely and carried out monitoring and evaluation, as well as carrying out financial control in almost every financial management carried out. In carrying out financial control, not all control is carried out by the official office, it only focuses more on the amount of budget spent and the amount of remaining budget.